2019
DOI: 10.3126/ajms.v10i6.25593
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers in pulmonary tuberculosis patients in Gombe, North-eastern Nigeria

Abstract: Background: Oxidative stress may play an important role in the pathogenesis of pulmonary tuberculosis (PTB). To our knowledge there is paucity of data on the status of oxidative stress biomarkers among PTB patients in Gombe, North-eastern Nigeria. Our study was designed to evaluate the oxidative stress biomarkers in pulmonary tuberculosis patients in Gombe, North-eastern Nigeria. Aims and Objectives: To determine the serum levels of oxidative stress biomarkers among patients with pulmonary tuberculosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a recent study it was observed that in patients of pulmonary tuberculosis the levels of anti oxidants decrease and that of oxidative stress biomarkers remarkably increase as in Nigerian population 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study it was observed that in patients of pulmonary tuberculosis the levels of anti oxidants decrease and that of oxidative stress biomarkers remarkably increase as in Nigerian population 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in different pathological conditions, including inflammatory diseases, an imbalance between oxidation processes and antioxidant protection develops and results in oxidative stress 25 . High levels of free radicals cause damage to all cellular components, including modifications of proteins 27,28 .…”
Section: Main Group (N=24)mentioning
confidence: 99%
“…The reasons for these changes are debatable and require further studies. However, there are data that pulmonary TB and HIV/TB coinfection, as well as HIV-infection, are accompanied by increased oxidative stress biomarkers and decreased total antioxidant status, due to chronic inflammation and hypoxia [28][29][30] .…”
Section: Main Group (N=24)mentioning
confidence: 99%